SEJARAH DAN TOKOH-TOKOH TASAWUF PASCA WALISONGO DI NUSANTARA - Rendi Imam Saputra; Afaf Nibrosy (Jurnal Shaf, 2025)
Sufism has played a crucial role in the development of Islam in the Indonesian archipelago, influencing spiritual practices, education, and socio-cultural life. After the era of the Wali Songo, Sufi teachings did not decline but instead expanded through networks of tarekat scholars spread across various regions, particularly in Sumatra, Java, and Sulawesi. This study aims to examine the historical development of Sufism in the post-Wali Songo period and to identify key figures who contributed to the dissemination and strengthening of Sufi teachings in the archipelago. Using a qualitative-descriptive approach through literature review, this article discusses the roles of figures such as Syekh Abdurrauf Singkel (Syattariyah), Syekh Burhanuddin Ulakan (Minangkabau), Syekh Yusuf al-Makassari (Sulawesi), and KH Ahmad Rifa’i (Java). These scholars not only propagated their respective tarekat orders but also contributed to Islamic education and resistance against colonialism. The study finds that post-Wali Songo Sufism transformed into a deeply rooted cultural and social force that shaped the spiritual character of Muslim communities in Indonesia up to the present day.